Boosting basic-peptide separation through dynamic electrostatic-repulsion reversed-phase (d-ERRP) liquid chromatography. Issue 21 (27th March 2020) - Mazzoccanti, Giulia; Manetto, Simone; Bassan, Michele; Foschini, Alberto; Orlandin, Andrea; Ricci, Antonio; Cabri, Walter; Ismail, Omar H.; Catani, Martina; Cavazzini, Alberto; Gasparrini, Francesco
Abstract : A simple and effective chromatographic method has allowed unprecedented resolution of basic peptide and their related impurities, including the very challenging epimeric isobaric ones. Abstract : The application of a novel chromatographic approach to therapeutic peptides bearing basic amino acids in their structure allowed unprecedented resolution of their related impurities (including epimeric isobaric ones), resulting in a superior analytical tool for the evaluation of the quality of these drugs in the market.